Patriarchy, couple counselling and testing in preventing mother-to-child transmission of HIV in Zimbabwe - Chibango, Vimbai (HTS teologiese studies, 2023)
The World Health Organization (WHO) recommends couple human immunodeficiency virus (HIV) counselling and testing (CHCT) as one of the beneficial and cost-effective means for the prevention of mother-to-child transmission (PMTCT) of HIV within couple’s relationships. However, CHCT within the PMTCT of HIV settings in Zimbabwe remains low. This study explored adult men and women’s views from a rural district of Zimbabwe regarding the possible factors that facilitate or inhibit the uptake of CHCT for the PMTCT of HIV. The study utilised qualitative methods. Data were collected by conducting eight focus group discussions among adult men and women, as well as eight in-depth interviews with pregnant women admitted in antenatal wards in local hospitals. Thematic analysis was used for analysing the data with the aid of NVivo software. The study revealed that CHCT initiatives were hampered by certain patriarchal behaviours and beliefs that make it acceptable for men to have multiple sexual partners, thereby exposing their marriages and relationships to HIV. Social constructions around gender roles tend to prescribe women as the sole custodians of children’s health, and this led to stigmatisation against men who participated in PMTCT programmes. In addition, certain religious practices do not allow the use of medicine, which makes CHCT a nonevent. However, engaging men on platforms that advocate for progressive masculinities and raising awareness of this practice through information dissemination were identified as enablers in increasing CHCT.Contribution: The significant contribution of this study is that it demonstrated the importance of acknowledging the societal, cultural and religious practices inherent in a community, as they are central to their responses to HIV prevention interventions.